HISTOLOGICAL STUDY ON THE PANCREATIC  -CELL NUMBER OF INDIGENOUS CHICKS IN FIRST CROSSBRED (F1) - Saragih, H.T.S.S.G.; Daryono, B.S. (Diponegoro University, 2010)
The objective of this study was to evaluate the total pancreatic -cell number of chicks in firstcrossbred (F1) with potential as broiler. The total number of twenty day-old male chicks consisted ofDOCs Cobb 500 broiler line as a control group and those of Pelung and the crossbred of Pelung andCemani chicks with the average body weight of 30 gram as materials. They were divided into fourgroups, in which each group has 5 male DOC's. Group 1 was DOCs from parent of Cobb 500 broiler asthe control; Group 2 was DOCs from parent of Pelung; Group 3 was crossbred DOCs from male parentCemani line and female parent Pelung line; and Group 4 was crossbred DOCs taken from male parent ofPelung and female parent of Cemani. Chick body weight of each group was measured at 7th week.Histological process was carried out on five DOCs of each group previously raised until seven weeksold and at the end of experiment all chicks were euthanized for pancreatic organs, particularly tissuesamples of pancreas, made as histological preparates. Data from the histological probe on totalpancreatic -cell number was statistically analyzed using the ANOVA of One Way Classification, andthen followed by the LSD-test. Result of the study showed that average body weights of DOCs in thecontrol group of Cobb 500 (2770±58.31) significantly higher (P<0.05) compared to the groups of 2, 3,and 4 (652.4±32.77, 570.4±14.45, and 628±37.2 g, respectively). Total pancreatic -cell number in thecontrol group of Cobb 500 broiler chicks (2.76x106±0.20x 106) significantly higher compared to thegroups of 2, 3, and 4 (1.93 x106±0.34 x106, 1.64x106±0.30x106, and 1.71 x106±0.19 x106, respectively).The results of this study revealed that total pancreatic -cell number can be used as an indicator of thegrowth and development of chick.